The Optimum Tariff: A formal approach and four observations - Coaguila, Jonathan (2007)
Considering that only the State has an interest in an equitable distribution of wealth, the authors determine a tariff that maximizes tax collection and minimizes the loss of efficiency. They then examine particular aspects of the emergence and application of tariffs.